Filosofi Tari Barong dan Relevansinya terhadap Kemampuan Berbahasa Siswa - Tri Linda Antika; Hanny Uswatunnisa; Novy Yuliyanti (JURNAL PENELITIAN PENDIDIKAN BAHASA DAN SASTRA, 2024)
The island of Bali is an island rich in culture and art, one of which is Barong. Barong Dance has a charm as one of the supports for the existence of culture and tourism in Bali. This study uses a descriptive qualitative approach to explore the philosophy of Barong Dance and its relationship with the development of language skills of junior high school students. The design of the case study research takes into account the uniqueness of the culture and philosophical meaning of the Barong Dance. Data was obtained through interviews with language teachers, dance coaches, cultural experts, and students, as well as direct observation of Barong Dance practices. The data was analyzed by identifying key themes such as collaboration, expression, and narrative, which are relevant for the development of students' language skills. The research subjects were selected by purposive sampling to obtain in-depth data. This research aims to uncover the philosophy of Barong Dance and its impact on speaking, listening, and argumentation skills, as well as provide recommendations for the integration of local cultural arts in the language education curriculum. The results of the study show that Barong Dance has significant relevance to students' language skills. As a non-verbal communication medium, this dance helps students develop speaking, listening, and argumentative skills. Learning Barong Dance also improves students' understanding of cultural values and moral philosophies that can be applied in daily life. In addition, this dance strengthens students' confidence in communicating. The concept of integrating Barong Dance in learning in schools supports the development of students' language skills and social-emotional aspects.